Preclinical Models for Acquired Resistance to Third-Generation EGFR Inhibitors in NSCLC: Functional Studies and Drug Combinations Used to Overcome Resistance - Mahfoudhi, Emna; Ricordel, Charles; Lecuyer, Gwendoline; Mouric, Cécile; Lena, Hervé; Pedeux, Rémy (Frontiers in Oncology, 2022)
Several clinical and preclinical studies are being carried out to identify the mechanisms of resistance to third generation EGFR-TKIs. Preclinical models have revealed a great heterogeneity of resistance mechanisms that non-small-cell lung cancer (NSCLC) could take advantage of. Resistance to third-generation EGFR-TKIs may be related to the activation of alternative signaling pathways by activation of tyrosine kinase receptors or to histological and phenotypic transformations. However, the mechanisms observed at the origin of these resistances have not the same prevalence in patients and in cell lines-based models. While EGFR mutations are among the most common in patients, they are absent in preclinical models. Likewise, NRAS genetic alterations are not observed in patients but have been described in cell lines resistant to third generation EGFR-TKIs. The preclinical models have made it possible to understand, in part, the complex network between the dominant drivers and the associated events that lead to the emergence of resistance and consequently to identify new therapeutic targets. Efforts, must, however continue to explore, in particular, the non-genetic control of this network, which has not yet been well characterized. This review provides an overview of preclinical studies developed to investigate the mechanisms of acquired resistance to 3rd G EGFR-TKIs, including osimertinib and rociletinib, regardless of the line of treatment. In fact, some of the models described were first generated to be resistant to first and second-generation EGFR-TKIs and often carried the T790M mutation, while others had never been exposed to TKIs. The review also provides the therapeutic opportunities in order to overcome the resistance, based on preclinical studies.